IMPLEMENTASI GREEN ACCOUNTING DI INDONESIA - Siti Nur Reskiyawati Said (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2025)
Environmental pollution caused by human and industrial activities has led to various environmental problems that may disrupt ecosystem balance and threaten the sustainability of living organisms. One approach that can support environmental management is the implementation of green accounting or environmental accounting. This study aims to analyze the implementation of green accounting in Indonesia and to identify its benefits and challenges based on previous research findings. The research employed a literature review method by examining various scientific sources, including journal articles, books, and other academic publications relevant to the topic. The findings indicate that the implementation of green accounting helps companies identify and disclose environmental costs, improve environmental information transparency, and support environmental management evaluation and business sustainability. However, its implementation still faces several challenges, including difficulties in measuring environmental costs, the absence of standardized reporting guidelines, andlimited corporate transparency in disclosing negative environmental information. Therefore,stronger corporate commitment and more comprehensive regulatory support are needed to promote the effective implementation of green accounting in Indonesia.